2019
DOI: 10.1039/c9ra05707b
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating PES/SPSF membrane via reverse thermally induced phase separation (RTIPS) process to enhance permeability and hydrophilicity

Abstract: A new method is presented to prepare hydrophilic PES/SPSF flat-sheet membrane by a reverse thermally induced phase separation (RTIPS) method to enhance permeability and hydrophilicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…As seen in the Figure, the SEM micrographs indicate that the addition of C60-ZSM-22 zeolite additives has pretentious significance on the morphological and structural forms of the PES membranes. This can be ascribed to the observed reduction in pore size (as manifested by the formation of smaller pores than in the pure PES substrate) and intensification of the pore densities as wt.% zeolite loadings increase, which is also observed elsewhere [65]. This shows that C60-ZSM-22 zeolite loading into the PES matrix has contributed to the development of membranes with high porosity, which protracts all through the membrane surface.…”
Section: Scanning Electron Microscopy (Sem) Surface Analysissupporting
confidence: 63%
“…As seen in the Figure, the SEM micrographs indicate that the addition of C60-ZSM-22 zeolite additives has pretentious significance on the morphological and structural forms of the PES membranes. This can be ascribed to the observed reduction in pore size (as manifested by the formation of smaller pores than in the pure PES substrate) and intensification of the pore densities as wt.% zeolite loadings increase, which is also observed elsewhere [65]. This shows that C60-ZSM-22 zeolite loading into the PES matrix has contributed to the development of membranes with high porosity, which protracts all through the membrane surface.…”
Section: Scanning Electron Microscopy (Sem) Surface Analysissupporting
confidence: 63%
“…For example, in a PES/SPSf polymer blend membrane system, increasing the SPSf content in the range 0-4 wt% increased the surface roughness. 40 Several researchers have demonstrated an increase in the surface roughness in mixed matrix PES/SPSf systems. For example, Gumbi et al also demonstrated that increasing the oxidized MWCNT wt% in the range 0-0.1 wt% a PES/SPSf system resulted in increased surface roughness.…”
Section: Atomic Force Microscopy Analysis Of Membranes Active Surfacementioning
confidence: 99%
“…He also developed full-biobased nanofiltration membranes. 16 (PVB), 25 poly(ethylene) (PE), 26 polyethersulfone (PES), 27 polypropylene (PP), poly(ethylene-co-vinyl alcohol) (EVOH) 28 and other polymers. 29 Although TIPS needs extra thermal energy compared with NIPS, it also brings several advantages.…”
Section: Ivomentioning
confidence: 99%